KONDISI STOK IKAN KARANG DI KAWASAN KONSERVASI PERAIRAN TWP GITA NADA, PROVINSI NUSA TENGGARA BARAT: Stock Condition of Coral Fish in Marine Protected Area at TWP Gita Nada, West Nusa Tenggara Province - Anas, Azwar; Gigentika, Soraya; Marliana, Isnaini; Aini, Muslihuddin; Hilyana, Sitti; Nurliah (Bogor Agricultural University, 2023)
TWP Gita Nada is one of the water conservation areas in NTB Province whose reef fish resources are used by fishers around the area, especially in zones that are permitted for fishing activities. However, there are indications that the use of the area by fishers causes a decrease in the abundance and biomass of reef fish in TWP Gita Nada. Therefore, it is necessary to research the condition of reef fish stocks in TWP Gita Nada to know for certain about the availability of reef fish resources in the area. This study collected data at 11 fish landing sites around TWP Gita Nada from March 2017 to December 2021. Data were collected using a sampling technique on 35% of the total fish landing activity in TWP Gita Nada. Data consisted of fishing units, fishing operations, fishing areas, catches, fish species, and fish length. Data analysis in this study used a length-based stock assessment approach to identify the condition of reef fish stocks and their utilization status. The results indicated that 271 species of reef fish landed in the TWP Gita Nada waters conservation area were identified from 31 family groups dominated by fish of the species Lutjanus gibbus, Lethrinus ornatus, Acanthurus mata, Naso thynnoides, and Lethrinus rubrioperculatus. Among those four dominant reef fish species, Lutjanus gibbus is in fully exploited utilization status with an SPR value of 0.26 or 26%. Meanwhile, the other three types of reef fish are under-exploited with SPR values above 0.3 or 30%. Keywords: fishing, Lc, length-based approach, Lm, SPR.